PENGARUH PEMBERIAN TABLET BESI DAN VITAMIN E PADA KADAR HEMOGLOBIN DAN STATUS BESI WANITA USIA SUBUR YANG DIDUGA MENDERITA THALASEMIA KARIER - M. Saidin; Sukati Sukati; Muherdiyatiningsih Muherdiyatiningsih; Effendi Rustan (Persagi, 2003)
THE EFFECT OF IRON PILL SUPPLEMENTATION ADDED WITH VITAMIN E (ALPHA-TOCOPHEROL) TO HEMOGLOBIN AND IRON STATUS OF CHILDBEARING AGE WOMEN SUSPECTED SUFFERING FROM CARRIER THALASSEMIA.Background: Anemia control programme among pregnant women had been conducting for about three decades, but prevalence of anemia still considered high. It was reported by Nutrition and Food Research Centre (2000) that 37.4% of childbearing women indicated fragility of red blood cell membrane wich assumed related to anemia. One of the vitamins which have positive effect to the wall of red blood cells is vitamin E through its rolle as antioxidant. It was recommended to conduct a study to determine the effect of supplementation of iron pill,